A dime a dozen eaudiobook Million dollar mysteries (clark) series, book 3. - Starns Clark, Mindy (Million Dollar Mystery, 2015)
ECPA best-selling author Mindy Starns Clark continues her Million Dollar Mystery series with A Dime a Dozen. Private investigator Callie Webber finally meets her boss, and is immediately smitten. But the romance must wait until she solves another mystery, this time involving her late husband's family. Callie can only hope that her prayers will be answered.